Association of Restless Legs Syndrome in Type 2 Diabetes: A Case-Control Study - Merlino, Giovanni (Associated Professional Sleep Societies, LLC, 2007)
STUDY OBJECTIVE: To look for an association between restless legs syndrome (RLS) and type 2 diabetes in a case-control study; to analyze the characteristics of RLS in diabetic patients; and to identify possible risk factors for the development of RLS in diabetic patients. DESIGN: A case-control study. SETTING: Diabetic outpatient clinic of a major university hospital. PARTICIPANTS: One hundred twenty-four consecutive outpatients with diabetes and 87 consecutive controls with a previous diagnosis of other endocrine disease. INTERVENTIONS: RLS was diagnosed using the criteria of the International RLS Study Group, and severity of RLS was assessed using the International RLS Study Group Rating Scale. Characteristics of RLS and several laboratory parameters were investigated in diabetic patients and controls affected by the sleep disorder. A clinical diagnosis of polyneuropathy was assessed to evaluate its role as a risk factor for RLS in diabetic patients. MEASUREMENT AND RESULTS: RLS was diagnosed in 22 diabetic patients (17.7%) and in only 5 controls (5.5%), 3 of whom had pituitary and 2 had adrenal gland disorders, and RLS was independently associated with type 2 diabetes (P < 0.04). Even if a clinical diagnosis of polyneuropathy was made in only 27% of diabetic patients affected by RLS, after multivariate logistic regression, the presence of polyneuropathy was the only variable associated with RLS in diabetics (odds ratio, 7.88; 95% confidence interval, 1.34–46.28; P < 0.02). RLS in diabetics showed a frequency of positive family history lower than that known for primary RLS, showed a late age of onset, and manifested itself after the diagnosis of diabetes was made. CONCLUSIONS: This is the first controlled study confirming a significant association between RLS and type 2 diabetes. In diabetic patients, polyneuropathy represents the main risk factor for RLS. However, polyneuropathy only partially explains the increased prevalence of RLS in type 2 diabetics. Clinical characteristics of RLS in diabetic patients are those of a secondary form. CITATION: Merlino G; Fratticci L; Valente M et al. Association of restless legs syndrome in type 2 diabetes: a case-control study. SLEEP 2007;30(7):866–871.